Virtual exchange and curricular internationalization: A case of a Spanish scholar’s experience in Brazil - Schaefer, Rodrigo; Manchado-Nieto, Cristina (Journal of International Students, 2025)
The interconnectedness of language, culture, and education underscores the growing importance of internationalization in higher education. This study explores the role of virtual exchange in advancing curricular internationalization through the experience of a Spanish PhD candidate participating in a virtual mobility program in Brazil. Employing a qualitative research design, the study draws on responses to 11 open-ended questions completed by the visiting scholar at the conclusion of the program. Data were analyzed using content analysis facilitated by Atlas.ti software, resulting in twelve emergent codes aligned with five established categories: academic, sociocultural, linguistic, professional, and personal dimensions. Findings highlight the mutual benefits of virtual academic mobility, emphasizing the enriching experience for the participant and its broader implications for fostering global partnerships and enhancing internationalization efforts within the curriculum of host institutions.